Within-session delay-of-reinforcement gradients. - Reilly, Mark P (2004)
Within-session delay-of-reinforcement gradients were generated with pigeons by progressively increasing delays to reinforcement within each session. In Experiment 1, the effects of imposing progressive delays on variable-interval and fixed-interval schedules were investigated while controlling for simultaneous decreases in reinforcer rate across the session via a within-subject yoked-control procedure. Rate of key pecking decreased as a negatively decelerated function of delay of reinforcement within a session. These rate decreases were greater than those during a yoked-interval session in which the rate of immediate reinforcement decreased at the same rate as it did under the progressive-delay procedure. In Experiment 2, delay-of-reinforcement gradients were shallower when the progressive delay intervals were signaled by a blackout than when they were unsignaled. The delay gradients obtained in each experiment were similar to those generated under conditions in which different delays of reinforcement are imposed across blocks of sessions. The present procedure offers a technique for rapidly generating delay-of-reinforcement gradients that might serve as baselines for assessing the effects of other behavioral and pharmacological variables.